Bioprospecção de atividades biológicas do Rhizopus sp. - LEITÃO, Valéria Maria Sousa (2024)
Introduction: Fungi are recognized as a great source of bioactive metabolites with great medical and pharmaceutical applicability. Rhizopus sp has applications in the food industry for biovaluation of products. Objectives: Produce fungal extract from Rhizopus sp identify secondary metabolites obtained from the extract; microemulsion preparation from Rhizopus sp extract to characterize the antioxidant, antimicrobial and cytotoxic activity against cervical adenocarcinoma tumor lines (HeLa and SiHa), Vero, Caco-2, PC-3 and B16-F10 cells. Methodology: The extracellular (oil) and intracellular (mycelial biomass) extracts were lyophilized, the latter incorporated into microemulsion. Mass spectrometry (Orbitrap-MS) combined the meatbolites present in the biomass extract. The determination of phenolics is determined using the Folin-Ciocalteu quantitative colorimetric method; The antimicrobial activity was evaluated against strains of Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella, Candida albicans, Candida parapsilosis and Candida tropicalis. Antioxidant activity was evaluated using the ABTS and DPPH method. The MTT for cytotoxic activity. Results: 13 metabolites were obtained, highlighting sorbitol, linoleic acid, oleic acid, palmitic acid and stearic acid. The Microemulsion with Rhizopus sp Biomass exhibited a higher amount of flavonoids and total phenolic compounds, compared to the biomass extract of Rhizopus sp and the extracellular extract of Rhizopus sp. The microemulsion formulated with biomass extract was the byproduct that changed the most from the control (gentamicin), and which also showed greater antioxidant activity. The extracts revealed strong/great antifungal action against different species of candida, optimized in the microemulsion formulation. The biomass extract revealed a cytotoxic effect on HeLa cells (IC50 of 56.22 μg/mL). Conclusion: The fungus Rhizopus sp constitutes a rich source of secondary metabolites with potential pharmacological activity that includes antimicrobial, antioxidant and cytotoxic effects related to cervical cancer. The microemulsion was shown to have an effective pharmacological presentation in preserving the metabolites obtained from the fungal extract, and also potentiating all evaluated activities except antitumor activity.